Engineering Practices of Determining Transmission Capacity and Delay of Interconnecting Line Taking into Account its Configuration and Cost - Igor Parkhomey; Juliy Boiko; Nataliia Tsopa; Oleksander Eromenko (IAES Indonesian Section, 2020)
This article contains information on engineering practice of determining transmission capacity of computer network line. The article presents a variant of engineering synthesis of computer network, which is a combined process of mathematical and heuristic methods combining. The engineering synthesis is offered as vector and global, because it must result in network development, optimal in terms of its practical use. All the significant network quality indicators, including economic and practical, are taken into consideration. In case of engineering synthesis, it is not possible that only one quality indicator is significant: there are always at least two significant indicators – a cost and an indicator that characterizes the main effect that is achieved in case of network use (efficacy). If at least one of the quality indicators significant for practical use is not taken into account, such network cannot be considered optimal. Computer network synthesis usually consists of structure synthesis, parameters optimization and discrete network selection. If network topology is maintained unchanged, it is possible to formulate an optimization task for line transmission capacity. The solution of transmission capacity task, which is constantly changing, may be chosen as a starting point for the selection of discrete indicator of transmission capacity.